Successful recellularization of human tendon scaffolds using adipose‐derived mesenchymal stem cells and collagen gel. (19th June 2012) - Martinello, Tiziana; Bronzini, Ilaria; Volpin, Andrea; Vindigni, Vincenzo; Maccatrozzo, Lisa; Caporale, Giovanni; Bassetto, Franco; Patruno, Marco
Abstract The major goal of regenerative medicine is to determine experimental techniques that take maximal advantage of reparative processes that occur naturally in the animal body. Injection of mesenchymal stem cells into the core of a damaged tendon represents such an approach. Decellularization of native tendons as potential targets and seeding protocols are currently under investigation. The aim of our study was to manufacture a recellularized biocompatible scaffold from cadaveric tissue for use in total or partial tendon injuries. Results showed that it was possible to introduce proliferating cells into the core of a decellularized tendon to treat the scaffold with a collagen gel. The method was effective in maintaining scaffold extracellular matrix and for expressing collagen type I and cartilage oligomeric matrix protein by injecting mesenchymal stem cells. Copyright © 2012 John Wiley & Sons, Ltd.